Design and construction of a teaching prototype for the study of control strategies applied to the ventilation of gas in underground mines (2014)
this paper shows the design and construction of a teaching prototype for the study and control of gas generation in mines. It is organized in the following way: review of the state of the art on the sensing of gases of mines ventilation, description of prototype, obtaining of the curve of reaction of the response of the gas sensors, desing and implementation of the control strategy, analysis of results and conclusions.